Association of DRD4 exon III and 5-HTTLPR VNTR genetic polymorphisms with psychiatric symptoms in hemodialysis patients. - Osama Y Alshogran; Laith N Al-Eitan; Shoroq M Altawalbeh; Hatem A Aman (PLoS ONE)
Mental illness is prevalent among hemodialysis (HD) patients. Given that the dopaminergic and serotonergic pathways are involved in the etiology of psychiatric disease, this study evaluated the genetic association of dopamine D4 receptor (DRD4) and serotonin transporter (SLC6A4) genes with psychiatric symptom susceptibility among HD patients. Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety and depressive symptoms among patients (n = 265). Genetic polymorphisms of DRD4 (48 bp VNTR) and SLC6A4 (5-HTTLPR VNTR and rs25531) were examined using a conventional polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) technique, as appropriate. Significant differences were observed in the distribution of 5-HTTLPR genotypes, SLC6A4 tri-allelic-phased genotype, and DRD4-Exon III VNTR genotypes/alleles between patients with anxiety symptoms versus those with normal/borderline conditions (p<0.05). Binary logistic regression analyses showed that the heterozygous 4,5 VNTR genotype of DRD4 was associated with a higher risk of anxiety symptoms after adjusting for other covariates (odds ratio = 4.25, p = 0.028). None of the studied polymorphisms was linked to depression in HD patients. Collectively, the current findings provide genetic clues to psychopathology in HD patients and suggest that the DRD4 exon III VNTR polymorphism is involved in the etiology of anxiety in this patient population.